Clinical application of platelet-rich fibrin as the sole grafting material in periodontal intrabony defects - Yu-Chao Chang; Kuo-Chin Wu; Jiing-Huei Zhao (Elsevier, 2011)
Background/purpose: Platelet-rich fibrin (PRF) obtained by Choukroun's technique is a healing biomaterial that concentrates in a single autologous fibrin membrane, mostly of platelets and cytokines from blood harvest, and without any artificial biochemical modification. However, no data are presently available concerning the use of PRF for the treatment of periodontal intrabony defects. This report was to present the clinical and radiographic changes of a patient with periodontal intrabony defects treated with PRF. Material and methods: The left mandibular first molar (#36) and left maxillary second molar (#27) with intrabony defects were filled with PRF as the sole grafting material in a 38-year-old female patient. The primary outcomes evaluated in this study included changes in probing depth, attachment level, and radiographic bone density between baseline and 6 months postoperatively. Results: The results showed that the application of PRF as the sole grafting material in intrabony defects exhibited pocket reduction and gain in clinical attachment after 3 months and 6 months. Using National institute of health program, the 6 months postoperative radiographic density of images for #27 and #36 showed an increase of 1.6 and 1.3 fold compared with each preoperative radiography, respectively. Conclusions: From a clinical and radiologic point of view at 6 months after surgery, the use of PRF as the sole grafting material seems to be an effective modality of regenerative treatment for periodontal intrabony defects.